2010
DOI: 10.1016/j.jiph.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Saudi Arabia: Can we change the way we deal with the disease?

Abstract: Infection from Mycobacterium tuberculosis results in the death of three million people worldwide per annum of which an estimated one thousand are in Saudi Arabia. The WHO has set a target for successful treatment of 85% but Saudi Arabia is currently not meeting that target. We believe that the first step in improving the control of tuberculosis in Saudi Arabia is to improve and unify the standards of diagnostic services and laboratories responsible for tuberculosis. This paper reviews the current status and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…CAS has also been identified as predominant family in Saudi Arabia (22.5%) and also the predominance of Delhi genogroup in Iran [23, 24] was reported. In Pakistan this lineage represents 61% of the total [25].…”
Section: Discussionmentioning
confidence: 99%
“…CAS has also been identified as predominant family in Saudi Arabia (22.5%) and also the predominance of Delhi genogroup in Iran [23, 24] was reported. In Pakistan this lineage represents 61% of the total [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TB infection in Jeddah (the main sea and airport for pilgrims arriving into Mecca) can reach up to 64 cases per 100,000, compared with 32 per 100,000 in central regions like Riyadh. The higher rate in Jeddah may have been caused by influx of pilgrims [3], [4]. Qureshi et al [5] observed that cough was the most common complaint, affecting more than 50% of pilgrims, and also that the commonest cause of pneumonia among hospitalized pilgrims visiting Saudi Arabia during the Hajj was TB [6].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that international travel, migration and movement of populations can facilitate the spread of TB. Saudi Arabia has a unique population dynamic, as annually, more than two million pilgrims visit the country for the Hajj pilgrimage, and, in addition, more than six million expatriates living in Saudi Arabia come from endemic areas [3]. This study was undertaken to identify the proportion of TB cases due to the non-Saudi population and to estimate the impact of poorly screened expatriates working here on the tuberculsosis burden in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…The overall TB incidence rate in KSA is approximately 16/100,000 and the death rate is approximately 1000 per annum; the incidence among Saudi nationals is 12/100,000 compared to 25/100,000 among non-nationals [3]- [8]. BCG vaccination is compulsory at birth in KSA, and TB treatment is free in government hospitals.…”
Section: Introductionmentioning
confidence: 99%